2003
DOI: 10.1053/jhep.2003.50478
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of HCV-specific Patr class II restricted CD4+ T cell responses in an acutely infected chimpanzee

Abstract: Resolution of hepatitis C virus (HCV) infection is associated with strong and sustained virus-specific CD4؉ T cell responses. In this study, we investigated the evolution of functional T cell responses during acute infection of a chimpanzee and the longevity of these lymphocytes in blood and liver after resolution of infection. Viremia increased through the first 3 weeks of infection and then remained stable until the onset of T cell responses at weeks 6 and 8 postinfection. CD4؉ T cells targeting nonstructura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 24 publications
(47 reference statements)
1
34
0
Order By: Relevance
“…Immune responses to the six mapped epitopes (Table II) were monitored by IFN-␥ ELISPOT analysis on cryopreserved PBMCs collected at different time points during primary infection. In addition, we monitored the immune response to a Patr-DRB5*0310-restricted epitope identified in another animal and designated NS3 1380 (1380-YGKAIPLEVI-1389) (31). Similar to what we and others have reported previously, there was a marked delay in the generation of HCV-specific immune responses despite robust virus replication (16,17,23,26).…”
Section: Tracking the Development Of Helper Responses During Primary supporting
confidence: 54%
“…Immune responses to the six mapped epitopes (Table II) were monitored by IFN-␥ ELISPOT analysis on cryopreserved PBMCs collected at different time points during primary infection. In addition, we monitored the immune response to a Patr-DRB5*0310-restricted epitope identified in another animal and designated NS3 1380 (1380-YGKAIPLEVI-1389) (31). Similar to what we and others have reported previously, there was a marked delay in the generation of HCV-specific immune responses despite robust virus replication (16,17,23,26).…”
Section: Tracking the Development Of Helper Responses During Primary supporting
confidence: 54%
“…It defines the development of T helper 1 (Th1) cells and is critical for host defense against a variety of intracellular pathogens, including HCV. IFN-␥ efficiently inhibits HCV replication in the replicon system in vitro (6) and the intrahepatic level of IFN-␥ appears to be associated with viral clearance in the chimpanzee model (7). The human IFN-␥ gene on chromosome 12q24.1 spans Ϸ5.4 kb and contains four exons that encode a 146-aa protein.…”
mentioning
confidence: 99%
“…Serum alanine aminotransferase (ALT) levels have been used in HCV studies to assess hepatocyte destruction by CD8 ϩ cytotoxic T cells (14,20,29,33). ALT levels were not elevated in marmosets M839 and M848 following infection (15), indicating that noncytolytic mechanisms may have been responsible for the control of viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…HCV infection studies with chimpanzees have shown that virus-specific T-cell responses are associated with viral clearance (9,31,33) and are able to respond rapidly to viral antigen when an animal is rechallenged (2,14,29). The duration and magnitude of viremia in the secondary infection are reduced in comparison to those of the primary infection and are associated with the rapid induction of memory CD4 ϩ and CD8 ϩ T cells (29).…”
Section: Reinfection Of Marmosets With Gbv-bmentioning
confidence: 99%